KARAKTERISTIK DAN MOTIVASI WISATAWAN DOMESTIK PENGGUNA LOW COST CARRIER PADA MASKAPAI PENERBANGAN LION AIR DI BANDARA INTERNASIONAL NGURAH RAI BALI - Sri Puspa Dewi, Roels Ni Made; Oka Karini, Ni Made; Eka Mahadewi, Ni Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 4 No 1 (2016): Jurnal IPTA (July 2016)DO - 10.24843/IPTA.2016.v04.i01.p09, 2016)
Low Cost Carrier has a tight competition, nowadays. There are more product offering to interest tourist which one is cheap ticket price or be familiar call Low Cost Carrier. Which one company in Indonesia applying Low Cost Carrier is Lion Air company. The aims of this study is to determine how the characteristics and motivation domestic tourists used Low Cost Carrier at Lion Air in Ngurah Rai International Airport Bali. The study was conducted at Lion Air. The object of this research was the characteristics and motivation of tourists who as means of transport choose Low Cost Carrier. Sample of respondents was 105 respondents. The collected data were observation, questionnaire, interview, literature study and documentation. The questionnaires was used as measuring the characteristics and motivation domestic tourists. The research was conducted using descriptive qualitative technique. The result of this research is domestic tourist characteristic used Lion Air divided into trip descriptor and tourist descriptor. By trip descriptor the tourist has short time to holiday around 3 untill 3 days with purposes of the trip is family trip with period using Lion Air around 2 untill more than 5 times. By tourist descriptor the tourists using Lion Air was teenager or adolescent with average income less than one million. Tourist motivation seen from push factor used Lion Air is cheaper ticket price while pull factor is there are more discount offering by Lion Air. Tourist motivation divided into intrinsic motivation and extrinsic motivation. Intrinsically, domestic tourist motivation used Lion Air by using Maslow theory is Social needs. While extrinsically is nowadays trends used airlines which applying Low Cost Carrier. Recommendation for Lion Air is to improve airlines network to avoid the delay of Lion Airlines.
Keywords: Characteristic, Motivation, Tourists, Low Cost Carrier